Listening Through Rock Salt: Quantifying Petrofabrics and Seismic Velocity Anisotropy of Evaporites to Improve Seismic Imaging - Heeb, Johanna (Curtin University, 2021)
Evaporitic rocksalt formations are polymineralic, structurally heterogeneous, and the minerals display fabrics crystallographic and shape preferred orientations. Both contribute to seismic velocity anisotropy to an unknown extend. A workflow including a new grain boundary intercept quantification method is presented and tested on numerical simulation with different phase content and strain geometry. Acoustic wave velocity of natural anhydrite samples was measured. Hydration of anhydrite was achieved for the first time under stress in triaxial experiments.